The subject and the beyond of meaning: between Heidegger and Lacan (Nóema, 2013)
The paper aims to establish a dialogue between some reflections by Heidegger and Lacan on the topic of subjectivity, with special emphasis on the relationship between meaning and what lies beyond meaning itself in the process of formation of subjectivity and its experiences. Going through several stages of analysis, and thus illustrating both the analogies and the differences between the two authors, I shall try and show that there exists more than a mere relationship of juxtaposition between the level of meaning and its beyond. The two levels stand instead in a relationship of reciprocal and differential implication, and it is thus possible to conceive of them as the two sides of the same event.
Keywords: Heidegger; Lacan; subjectivity; meaning; desire; jouissance; difference; world/earth; body; praxis